Judicial Reforms in Indonesia's Local Courts: Improving Access to Justice or Perpetuating Inequities? (Indonesian Court and Justice Review, 2025)
Judicial reform in Indonesia has long focused on central institutions, yet the performance of local courts remains a key determinant of citizens' everyday access to justice. This study investigates whether recent judicial reform initiatives—such as digitalization, case tracking systems, and integrated services—have improved the accessibility, fairness, and responsiveness of local courts. Using qualitative fieldwork in several district courts, combined with interviews and policy analysis, the research explores the impact of reform on marginalized communities, including rural populations and low-income litigants. While technological innovations have enhanced administrative efficiency and transparency, findings suggest that socio-economic and geographic disparities continue to shape unequal access to legal remedies. Key barriers include digital illiteracy, language limitations, and limited legal aid availability. Furthermore, local courts often reflect broader power imbalances, with elites receiving more favorable treatment. The novelty of this study lies in its localized, ground-level evaluation of judicial reform, highlighting how national-level policy often fails to account for structural inequities on the ground. The research argues that meaningful access to justice requires not only institutional modernization but also a justice system that actively addresses social inequality. This study contributes to ongoing discussions on legal empowerment and inclusive justice reform in decentralized legal systems.